Rifaximin treatment in patients with severe alcoholic hepatitis: A multicenter, randomized controlled, open-label, pilot trial - Do Seon Song; Jin Mo Yang; Young Kul Jung; Hyung Joon Yim; Hee Yeon Kim; Chang Wook Kim; Soon Sun Kim; Jae Youn Cheong; Hae Lim Lee; Sung Won Lee; Jeong-Ju Yoo; Sang Gyune Kim; et al. (Annals of Hepatology)
Introduction and Objectives: The short-term mortality of severe alcoholic-associated hepatitis (SAH) is high, but there are no effective treatments to improve short-term mortality other than corticosteroids. This study investigated the effects of adding rifaximin to standard treatment in patients with SAH. Material and Methods: In this randomized controlled open-label trial, patients with SAH (Maddrey's discriminant function≥32) were randomized to the rifaximin or control group. Patients were simultaneously treated with corticosteroid or pentoxifylline as standard treatment for 4 weeks. Randomization was stratified by SAH treatment. Results: A total of 50 patients were enrolled in this study (29 in the control group and 21 in the rifaximin group). The mean Model for End-stage Liver Disease (MELD) scores were 24.4 and 27.5 in the control and rifaximin groups, respectively (P = 0.106). There were no significant differences in 6-month Liver Transplantation (LT)-free survival rate between the two groups (P = 0.502). When stratified by SAH treatment, there was no significant difference in 6-month LT-free survival rate between the control and rifaximin treatment groups (P = 0.186 in the corticosteroid group and P = 0.548 in the pentoxifylline group). There were no significant differences in the occurrence of liver-related complications between the two groups (all Ps>0.05). The MELD score was the only independent factor for 6-month LT-free survival (hazard ratio 1.188, 95 % confidence interval 1.094-1.289, P<0.001), and rifaximin was not. Conclusions: In patients with SAH, adding rifaximin to corticosteroid or pentoxifylline had no survival benefit and no preventive effect on the development of liver-related complications. The MELD score was the only significant factor for short-term mortality. Clinical trial registration: The study was registered on ClinicalTrials.gov (number: NCT02485106).